Computer system “ProNRS” and three-dimensional modeling of distributing of temperatures, stresses and carbon in the process of continuous steel casting - A. N. Chichko; D. M. Kukuj; V. F. Sobolev; Ju. V. Jatskevich; S. G. Likhouzov; O. I. Chichko; E. A. Drozdov (Литьë и металлургия, 2002)
The authors are developing the new approach, based on the cellwise automatic modelling of the continuous steel casting process, allowing to calculate and visualize on computer the threedimensional process of cast slugs production in real industrial conditions.